Diphenyl diselenide differently modulates cardiovascular redox responses in young adult and middle-aged low-density lipoprotein receptor knockout hypercholesterolemic mice. (12th November 2013) - Mancini, Gianni; de Oliveira, Jade; Hort, Mariana Appel; Moreira, Eduardo Luiz Gasnhar; Ribeiro-do-Valle, Rosa Maria; Rocha, João Batista Texeira; de Bem, Andreza Fabro
Abstract: Objectives: The present work aimed to investigate the effect of (PhSe)2 on cardiovascular age-related oxidative stress in hypercholesterolemic mice. Methods: To this end, LDL receptor knockout (LDLr −/− ) mice, 3 months (young adult) and 12 months (middle-aged) old, were orally treated with (PhSe)2 . Key findings: Hypercholesterolemia, regardless of age, impaired the mitochondrial antioxidant defence in the cardiac tissue, which was characterized by a decline in mitochondrial aortic glutathione (GSH) levels and increased reactive oxygen species production in the heart. (PhSe)2 treatment improved GSH levels, thioredoxin reductase (TRxR) and GSH reductase (GR) activity, and decreased malondialdehyde levels in the heart of young adult LDLr −/− mice. Moreover, (PhSe)2 increased GPx activity in both age groups, and GR activity in the aorta of middle-aged LDLr −/− mice. Conclusions: Therefore, (PhSe)2 enhances the antioxidant defences in the cardiovascular system of LDLr −/− mice, which could explain its success as an anti-atherogenic compound.